Short-term student exchange using double loop learning framework of heutagogy - Chan, Cheong Jan; Wong, Siao Ern; Shien, Wei Lee; Rickard, Joshua; Toh, Phyllis Chze Woon; Mohamed Razali, Camellia Siti Maya (Human Resource Management Academic Research Society, 2022)
This paper traces the outcomes of an experimental student exchange program based on the concept of Heutagogy, self-determined learning. The program, which was carried out between Japanese and Malaysian students in 2018 and 2019 was aimed at challenging the traditional structure of a short-term exchange program, in which students might learn about a new culture in a limited top-down fashion, for one that favours deep interaction and reflection between participants in both societies. The program utilised online resources in order to create a longer period of interaction building up to the in-person exchange. Results were presented in an integrated model combining cultural adjustment levels with learning levels. The program has produced profound outcomes in providing real cross-cultural interactions and self-examination.